DAMPAK ZAKAT INFAQ DAN SEDEKAH TERHADAP KESEJAHTERAAN RUMAH TANGGA (Studi Pada LAZ EL-ZAWA Kota Malang) - Coky Sandra Pradana Achmad Gaffar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Amil Zakat Institute (LAZ) El-Zawa City of Malang through ZIS fund distribution program, in the form of UMKM program provides assistance in the form of business capital using Zakat, Infaq and Sedekah (ZIS) funds to household business owners (mustahik). With the help of venture capital along with systematic empowerment is expected to improve the welfare of the household. The objectives of this research are: To know the impact of ZIS funding on household welfare seen from Asset, Food Security and Financial Access level. The variables that represent these three indicators are income to represent Assets, consumption to represent Food Security, and savings to represent Financial Access. The approach used in this research is descriptive quantitative approach with the number of respondents as much as 33 samples of beneficiary households funding ZIS program UMKM LAZ El-Zawa Malang. The result pointed out that the mechanism that Laz El-Zawa carried out in the form of capital, supervision and training. Based on the results of different test analysis using SPSS21, showed that the impact of ZIS on welfare is a positive effect seen from 2 indicators of Asset and Food Security. However, negative results are shown from the Financial Acces indicator.Keywords: ZIS, Welfare, Income, Consumption, Savings